Organic Pollutants: An Ecotoxilogical Perspective - Walker, C. (CRC Press, 2009)
Organic pollutants continue to be a major hazard in the environment. Often difficult to measure accurately and to deal with effectively, these compounds feature more and more prominently in courses on environmental toxicology and environmental sciences. This much needed book is a companion to the highly praised Principles of Ecotoxicology. It covers organic pollutants in greater depth and detail than has been covered in a textbook before. The first part covers issues such as: · chemical warfare · metabolism of pollutants in animals and plants · environmental fate, and effects within ecosystems This is followed up with discussion of particular pollutants such as: · organochloride insecticides · PCBs · dioxins · organometallic compounds · polycyclic aromatic hydrocarbons · anticoagulant rodenticides amongst others The book concludes with coverage of ecotoxicity testing, biomarkers and bioassays and future prospects for improved assessment of the dangers these compounds pose. There is no other single, concise source of information on these compounds at a level suitable for senior undergraduates and postgraduates. Professionals working within the fields of environmental toxicology and environmental science will also find it a valuable reference.